Why do employees follow their superiors' instructions? Identification of the reasons to comply with superiors' will in a group of Polish employees - Aleksandra Wójcik; Dorota Merecz-Kot; Aleksandra Andysz (Nofer Institute of Occupational Medicine, 2015)
Background: Managers influence the way organization works as well as the functioning of subordinates - in the context of their work life but non-professional functioning as well e.g., attitude towards work-life balance or taking care of health. We focused on the superior-subordinate relation, referring to social power bases theory by Raven. We identified the reasons why subordinates decide to follow their superiors' orders and determined specific styles of compliance with superiors' will. Understanding why employees listen to their superiors may be valuable in the context of supporting healthy organizational climate and atmosphere of co-operation or communicating values - for example, as regards taking care of own health. We discussed the results referring to the issue of influencing employees in the context of their health behavior. Material and Methods: The research involved 100 Polish employees, aged 28 years old on average, who filled in the Interpersonal Power Inventory by Raven et al. for subordinates in a Polish adaptation by Zaleski. The questionnaire includes 11 subscales referring to power bases. Results: Based on the cluster analysis results, we recognized people who complied because of: all kinds of power bases (typical for 46% of the respondents); the respect for superiors' professionalism (34%); and formal/objective reasons (20%). Conclusions: Employees differ in terms of their styles of compliance. Their motives to comply with superiors' instructions constitute compilations of power bases. The superiors' awareness of the reasons why their employees decide to follow orders is necessary for successful management. It may motivate employees to work but also to take care of their own health. Med Pr 2015;66(5):605-614